Roles of collecting duct renin and (pro)renin receptor in hypertension: mini review. (August 2015) - Gonzalez, Alexis A.; Prieto, Minolfa C.
In angiotensin (Ang)-II-dependent hypertension, collecting duct renin synthesis and secretion are stimulated despite suppression of juxtaglomerular (JG) renin. This effect is mediated by Ang II type 1 (AT1) receptor independent of blood pressure. Although the regulation of JG renin is known, the mechanisms by which renin is regulated in the collecting duct are not completely understood. The presence of renin activity in the collecting duct may provide a pathway for intratubular Ang II formation since angiotensinogen substrate and angiotensin converting enzyme are present in the distal nephron. The recently named new member of the renin–angiotensin system (RAS), the (pro)renin receptor [(P)RR], is able to bind renin and the inactive prorenin, thus enhancing renin activity and fully activating prorenin. We have demonstrated that renin and (P)RR are augmented in renal tissues from rats infused with Ang II and during sodium depletion, suggesting a physiological role in intrarenal RAS activation. Importantly, (P)RR activation also causes activation of intracellular pathways associated with increased cyclooxygenase 2 expression and induction of profibrotic genes. In addition, renin and (P)RR are upregulated by Ang II in collecting duct cells. Although the mechanisms involved in their regulation are still under study, they seem to be dependent on the intrarenal RAS activation. The complexities of the mechanisms of stimulation also depend on cyclooxygenase 2 and sodium depletion. Our data suggest that renin and (P)RR can interact to increase intratubular Ang II formation and the activation of profibrotic genes in renal collecting duct cells. Both pathways may have a critical role in the development of hypertension and renal disease.